2009
DOI: 10.1111/j.1469-8137.2009.02920.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale parallel 454 sequencing reveals host ecological group specificity of arbuscular mycorrhizal fungi in a boreonemoral forest

Abstract: Summary• Knowledge of the diversity of arbuscular mycorrhizal fungi (AMF) in natural ecosystems is a major bottleneck in mycorrhizal ecology. Here, we aimed to apply 454 sequencing -providing a new level of descriptive power -to assess the AMF diversity in a boreonemoral forest.• 454 sequencing reads of the small subunit ribosomal RNA (SSU rRNA) gene of Glomeromycota were assigned to sequence groups by BLAST searches against a custom-made annotated sequence database.• We detected 47 AMF taxa in the roots of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
407
5
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(459 citation statements)
references
References 60 publications
(94 reference statements)
35
407
5
12
Order By: Relevance
“…Even fungi capable of colonizing numerous host species (e.g., arbuscular mycorrhizal fungi) often exhibit some degree of host specificity [10,[12][13][14], which can generate species-specific feedbacks that influence both above-and belowground community composition [2]. Since abiotic conditions can alter these plant-fungal feedbacks [11], rhizosphere communities also likely vary along environmental and habitat gradients [e.g., 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even fungi capable of colonizing numerous host species (e.g., arbuscular mycorrhizal fungi) often exhibit some degree of host specificity [10,[12][13][14], which can generate species-specific feedbacks that influence both above-and belowground community composition [2]. Since abiotic conditions can alter these plant-fungal feedbacks [11], rhizosphere communities also likely vary along environmental and habitat gradients [e.g., 15].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focus on AMF as an identifiable functional group within the overall rhizosphere community. Studies employing molecular methods to characterize AMF diversity indicate that a single host species can associate with as many as 38 AMF taxa [14]. However, many AMF appear to have limited geographic distributions [19,20] and exhibit varying degrees of host specificity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The small subunit rRNA gene was examined because it is the most widely used marker in field studies analysing AMF communities, also due to the availability of primer sets which are able to detect a wide range of glomeromycotan genera as well as the increasing number of available AMF sequences in GenBank following large-scale 454 pyrosequencing (Öpik et al 2009;. In particular, the NS31-AMmix primer set should allow the detection of Glomeraceae, Entrophosporaceae, Diversisporaceae, Acaulosporaceae, Gigasporaceae, Scutellosporaceae, Dentiscutaceae, Racocetraceae and Archaeosporaceae (Santos-González et al 2007;Schechter and Bruns2008).…”
Section: Each Primer Combination Contributes To Amf Diversity Descripmentioning
confidence: 99%
“…The use of DNA sequencing methods and high-throughput molecular tools has improved our understanding of the diversity of AMF, in particular because they have allowed AMF to be directly detected from environmental samples (Öpik et al 2009;Lumini et al 2010;Dumbrell et al 2011). Apparently, natural communities of AM fungi are biologically diverse, with large numbers of undescribed taxa.…”
Section: Introductionmentioning
confidence: 99%
“…By using molecular tools, recent case studies revealed overwhelming richness of tropical foliar endophytes (Arnold and Lutzoni, 2007). The relative biodiversity of arbuscular mycorrhizal fungi is similar in tropical and temperate regions (Husband et al, 2002;Ö pik et al, 2009). Local richness and community composition of biotrophic fungi, endophytes, mycorrhizal and hexapod symbionts, is largely driven by their host preference or specificity (Husband et al, 2002;Currie et al, 2003;Arnold, 2008).…”
Section: Introductionmentioning
confidence: 99%